Leaf shape evolution has a similar genetic architecture in three edaphic specialists within the Mimulus guttatus species complex - Ferris, Kathleen G. (Ann Bot, 2015)
Background and Aims The genetic basis of leaf shape has long interested botanists because leaf shape varies extensively across the plant kingdom and this variation is probably adaptive. However, knowledge of the genetic architecture of leaf shape variation in natural populations remains limited. This study examined the genetic architecture of leaf shape diversification among three edaphic specialists in the Mimulus guttatus species complex. Lobed and narrow leaves have evolved from the entire, round leaves of M. guttatus in M. laciniatus, M. nudatus and a polymorphic serpentine M. guttatus population (M2L). Methods Bulk segregant analysis and next-generation sequencing were used to map quantitative trait loci (QTLs) that underlie leaf shape in an M. laciniatus × M. guttatus F(2) population. To determine whether the same QTLs contribute to leaf shape variation in M. nudatus and M2L, F(2)s from M. guttatus × M. nudatus and lobed M2L × unlobed M. guttatus crosses were genotyped at QTLs from the bulk segregant analysis. Key Results Narrow and lobed leaf shapes in M. laciniatus, M. nudatus and M. guttatus are controlled by overlapping genetic regions. Several promising leaf shape candidate genes were found under each QTL. Conclusions The evolution of divergent leaf shape has taken place multiple times in the M. guttatus species complex and is associated with the occupation of dry, rocky environments. The genetic architecture of elongated and lobed leaves is similar across three species in this group. This may indicate that parallel genetic evolution from standing variation or new mutations is responsible for the putatively adaptive leaf shape variation in Mimulus.